Understanding human enhancement technologies through critical phenomenology. (30th October 2018) - Pariseau‐Legault, Pierre; Holmes, Dave; Murray, Stuart J.
Abstract: Human enhancement technologies raise serious ethical questions about health practices no longer content simply to treat disease, but which now also propose to "optimize" human beings' physical, cognitive and psychological abilities. These technologies call for a reassessment of our relationship to health, the human body and the body's organic, identity and social functions. In nursing, such considerations are in their infancy. In this paper, we argue for the relevance of critical phenomenology as a way to better understand the ethical issues related to human enhancement technologies (HET). In so doing, we seek to problematize HET and assess their influence on the future development of nursing science and practice. It is difficult to anticipate the concrete effects of HET, we suggest, because these practices reconfigure the meaning of normativity and disorient our conventional ethical landscape. In this context, we argue that the later work of Martin Heidegger and Michel Foucault invites a critical perspective into how techno‐scientific discourses modify our relationship to care, to health and to our own social and corporeal identities. Despite the traditional philosophical opposition between phenomenology and critical theory, we maintain that a hybrid critical phenomenological approach opens new ways to assess the integration of technology and practice. Our analysis understands HET as a process of "hybridization" between technological objects and human subjects. Critical phenomenology thus effectively questions anthropocentric definitions of technology, challenges the dichotomy between curative treatment and enhancement and, finally, prompts valuable reflection on the implications of HET for nursing theory and practice.